Failure Mechanism Analysis and Failure Number Prediction of Wind Turbine Blades - Yu Chun-yu; Guo Jian-ying; Xin Shi-guang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Pertinent to the problems that wind turbine blades operate in complicated conditions, frequent failures and low replacement rate as well as rational inventory need, this paper, we build a fault tree model based on in-depth analysis of the failure causes. As the mechanical vibration of the wind turbine takes place first on the blades, the paper gives a detailed analysis to the Failure mechanism of blade vibration. Therefore the paper puts forward a dynamic prediction model of wind turbine blade failure number based on the grey theory. The relative error between its prediction and the field investigation data is less than 5%, meeting the actual needs of engineering and verifying the effectiveness and applicability of the proposed algorithm. It is of important engineering significance for it to provide a theoretical foundation for the failure analysis, failure research and inventory level of wind turbine blades.